2014
DOI: 10.1016/j.jegh.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in semi-urban communities in southwest Nigeria: Patterns and prevalence

Abstract: High prevalence of cardiovascular risk factors call for an urgent need for more public health attention and reinforcement of primary preventive strategies to curb its menace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 19 publications
(31 reference statements)
7
31
1
Order By: Relevance
“…This finding agrees with other studies on independent CVD risk factors, which showed an increase in prevalence with increase in age [36, 37]. No significant predicted age difference was observed in population with and without IFG and IFG co-morbidity with risk factors, except in overweight/obese.…”
Section: Discussionsupporting
confidence: 92%
“…This finding agrees with other studies on independent CVD risk factors, which showed an increase in prevalence with increase in age [36, 37]. No significant predicted age difference was observed in population with and without IFG and IFG co-morbidity with risk factors, except in overweight/obese.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were likely a result of the higher cut-off point for women than men in the definition. On the other hand, high prevalence of cardiovascular risk in women was also reported by other studies [47-49]. The higher prevalence of diabetes among females was also indicated in previous research [50, 51].…”
Section: Discussionsupporting
confidence: 79%
“…32 39 40 A repeated cross-sectional study reported an increase over time in the prevalence of hypercholesterolaemia in Dar es Salaam with a prevalence of 17% in 1987 vs 30% in 1998 in men, and 7% vs 50% in women. 39 The prevalence of hypercholesterolaemia in our sample was higher than that reported by studies conducted between 2008 and 2014 in rural Uganda (3% men, 8% women), 9 peri-urban Nigeria (2% men, 6% women) 8 and blacks in urban South Africa (25% men, 23% women), 41 but is lower than that reported in a study from Senegal (54% men, 61% women) that included both urban and rural participants. 42 Our estimated association between palm oil versus sunflower oil use and serum total cholesterol is consistent with findings from dietary observational studies and intervention trials.…”
Section: Discussioncontrasting
confidence: 72%
“…5 Sub-Saharan Africans have historically had a favourable lipid profile 6 but hyperlipidaemia is becoming increasingly common in these countries, especially in urban areas. [7][8][9] It is estimated that 34% of IHD deaths in Tanzania are attributable to dyslipidaemia. 10 A few studies have already explored the relationship between diet and serum total cholesterol in eastern sub-Saharan Africa…”
Section: Introductionmentioning
confidence: 99%